Barrier Resilience of Visibility Polygons (Informatica, 2015)
We consider the problem of computing the Barrier Resilience of a set of Visibility Polygons inside aPolygon. We show that in simple polygons the problem is solvable in time linear in the number of edges.In polygons with holes the problem is APX-hard, so only for special cases can we provide polynomial timealgorithms.